Companionate Marriage: Mary Wollstonecraft's Vision as a Cure to Divorce in a Women Empowered Society - Marimuthu Prahasan (Darul Yasin Al Sys, 2026)
Historically, women have occupied a subordinate position, with marriage and family structures perpetuating their social and economic dependence on men. The long struggle for women’s liberation has centered on securing access to education, employment opportunities, and social and economic independence as foundations for social status. Within this trajectory, feminist activists have played a pivotal role, with Mary Wollstonecraft emerging as a key figure who emphasized women’s social responsibilities and argued that, by virtue of their rational capacities, women merit equal recognition in society. Her advocacy for equality within the family structure was particularly influential in proposing that the Aristotelian concept of high-level friendship be applied to marriage—identified as “companionate marriage”—thereby positioning egalitarian marital relationships as a pathway to women’s greater status and equality. In the contemporary context, women’s increased empowerment and capacity for independent action, including greater willingness to leave marriages that no longer serve their interests, signal the autonomy they have gained but also raise questions about the rising incidence of divorce. This study examines the historical concept of marriage as a form of high-level friendship—originally advanced as a means of promoting gender equality—and investigates its potential application as a strategy for addressing contemporary divorce in a society where women are increasingly empowered. Conducted as a qualitative study using secondary data, it analyzes the notion of friendship as articulated in works such as A Vindication of the Rights of Woman and The Nicomachean Ethics. The findings indicate that Mary Wollstonecraft’s model for women’s advancement remains normatively robust and socially relevant, providing a conceptual framework for reimagining marriage as an egalitarian partnership that can respond to current gender and relational tensions. This philosophical exploration of divorce further underscores the need to dismantle patriarchal ideologies embedded in social structures so that marriage can function as a space of mutual respect, reciprocity, and shared flourishing.